Obesity among urban primary schoolchildren - A. Hamid, Mohamad Shariff; Shariff Ghazali, Sazlina; Shah, Shamsul Azhar (Faculty of Medicine, University of Malaya, 2007)
Three urban public primary schools in the district of Petaling, Selangor were surveyed for obesity amongst the schoolchildren and factors related to it. The prevalence of obesity amongst primary schoolchildren, with the mean age of 8.91 years was 9.5%. In addition, it was more prevalent among the boys (p<0.05) as compared to the girls. However, there was no difference with regards to ethnicity, being breastfed, physical activity, time spent watching television or fast food intake in relation to obesity among these primary schoolchildren. A larger community study is required to determine if other specific factors and dietary energy intake are associated with obesity amongst primary schoolchildren, especially in rural or less urbanised regions.